TIFAC-CORE in Green Pharmacy gathers momentum - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
The TIFAC-CORE in Green Pharmacy has now picked up momentum with 4 TCRP (TIFAC CORE Research Programs) and 3 industrial collaborations. The RMC (REACH Monitoring Committee) in its meeting held on July 7, 2008, under the chairmanship of Dr. V. S. Chauhan (Vice President, Nicholas Piramal) and membership of Dr. M. C. Sharma (Director, National Institute of Ayurveda), Dr. K. K. Bhutani (Dean, National Institute of Pharmaceutical Education and Research), and Dr. M. M. Padhi (Dy. Director, Combined Council of Research in Ayurveda and Siddha) approved conduction of TCRP in ‘Pharmaceutical Product Development,’ ‘Quality Assurance,’ ‘Intellectual Property Rights,’ and ‘Regulatory Affairs.’ The RMC also approved purchase of equipments worth Rs. 13 million in the first phase.